Leveraging process data from BPM cloud-based workflows - Ó Conchúir, Deasún; Dražeta, Lazar (The European Journal of Applied Economics, 2016)
This paper shares the experience of a virtual team of knowledge workers which coordinates its repetitive production work across 12 time zones using cloud-based workflows. A sample of process data and the utility that can be obtained from it are discussed, and recommendations are provided for the management of virtual teams using cloud-based workflows. In addition, possible directions for future research relating to virtual knowledge work teams using cloud workflows are suggested. Some references to related experience for further reading are also given